Performance, Politics, and the War on Terror - Brady, Sara. author. aut Link
XVII, 203 p.
Keywords: Using a performance studies lens, this book is a study of performance in the post-9/11 context of the so-called war on terror. It analyzes conventional theatre, political protest, performance art and other sites of performance to unpack the ways in which meaning has been made in the contemporary global sociopolitical environment.